PWE-153 Cost Effectiveness Of Rifaximin-a In The Reduction Of Recurrence Of Overt Hepatic Encephalopathy. (9th June 2014) - Poole, CD; Conway, P; Nanuwa, K; Joseph, B; Bannister, C; Currie, CJ
Abstract : Introduction: Hepatic encephalopathy (HE) is associated with high morbidity and mortality. Rifaximin-α is effective in reducing the recurrence of episodes of overt HE. The aim was to characterise the cost effectiveness of rifaximin-α versus standard care (lactulose). Methods: This economic evaluation used a Markov state transition model. The outcome was the incremental cost effectiveness ratio (ICER), derived from estimates of the cost/quality adjusted life years. The payer perspective was that of UK National Health Service. Outcome data were from two trials of rifaximin-α. Population outcome data were from a complementary study of patients with liver cirrhosis treated within the NHS. Cost data (GBP£2012) were derived from published sources. Health-related utility was estimated indirectly from disease-specific trial QoL data. The time horizon was five years. Costs and benefits were discounted at 3.5%. Extensive sensitivity analysis was carried out. Results: The average cost of the included elements of care was £15, 476 in the rifaximin-α arm and £4, 486 in the lactulose arm, a difference of £10, 990. The corresponding values for benefit was 2.36 QALYs, and 1.83 QALYs per person, respectively; a difference of 0.53 units. This translated into a base-case ICER of £20, 852/QALY. Key parameters that impacted the ICER included the event-free survival pattern, ranging from an ICER of £13, 919 using an exponential model, to £21, 425/QALY using a log-logistic model. Evaluation to 10 years resulted in an ICER of £19, 122/QALY. Conclusion: Rifaximin-α in patients with liver cirrhosis was cost effective compared to standard care, reducing episodes of overt hepatic encephalopathy. Disclosure of Interest: C. Poole Consultant for: Norgine, P. Conway Employee of: Norgine;, K. Nanuwa Employee of: Norgine, B. J, oseph Employee of: Norgine, C. Bannister Consultant for: Norgine, C. Currie Consultant for: Norgine.>